The influence of green marketing on brand affinity of select coffee shops: A moderated mediation analysis - Santos, Francia R. (Animo Repository, 2022)
This paper examined the influence of green marketing (GM) on coffee shops’ brand affinity (BA). It further investigated the mediating and moderating effects of digital advertising and greenwashing respectively. Respondents of this study involved 221 customers of the top four Brands of Coffee Shops in Metro Manila, Philippines. Predictive causal and quantitative research designs were employed to gauge the relationship between green marketing and brand affinity. Both direct and indirect effects of the moderating and mediating constructs had been analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS). This study hypothesized that green marketing significantly influences the brand affinity of coffee shops. Moreover, the hypotheses of the study included positive and direct relationships between sets of variables (green marketing and digital advertising; digital advertising and brand affinity). The call for global environmental sustainability and a marketing communications model as applied to coffee shops is addressed by this study. It presses on new perspectives emphasizing digital advertising as a mediating variable and greenwashing as a moderating factor. These bring to light the relationship between green marketing and the brand affinity of coffee shops.